2004
DOI: 10.1128/mcb.24.22.9942-9947.2004
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic Anhydrase III Is Not Required in the Mouse for Normal Growth, Development, and Life Span

Abstract: Carbonic anhydrase III is a cytosolic protein which is particularly abundant in skeletal muscle, adipocytes, and liver. The specific activity of this isozyme is quite low, suggesting that its physiological function is not that of hydrating carbon dioxide. To understand the cellular roles of carbonic anhydrase III, we inactivated the Car3 gene. Mice lacking carbonic anhydrase III were viable and fertile and had normal life spans. Carbonic anhydrase III has also been implicated in the response to oxidative stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 41 publications
3
65
0
Order By: Relevance
“…Our analysis of these genes revealed that they were expressed in the muscle tissue surrounding the joint. The slow muscle marker Car3 (Kim et al, 2004) and Csrp3, a marker of differentiated striated muscle (Arber et al, 1997) were found in the triceps and pronator muscles that insert into the ulna and are necessary for motion of the forelimb (Fig. 5C,D).…”
Section: Resultsmentioning
confidence: 99%
“…Our analysis of these genes revealed that they were expressed in the muscle tissue surrounding the joint. The slow muscle marker Car3 (Kim et al, 2004) and Csrp3, a marker of differentiated striated muscle (Arber et al, 1997) were found in the triceps and pronator muscles that insert into the ulna and are necessary for motion of the forelimb (Fig. 5C,D).…”
Section: Resultsmentioning
confidence: 99%
“…The significance of CAIII reduction on hepatocarcinogenesis in Sod1−/− mice is not clear. CAIII null mutant mice have been generated, and no obvious phenotype has been attributed to CAIII deficiency [38]. However, expression of Car3 in cells lacking the protein protects the cells from hydrogen peroxide-induced apoptosis [39].…”
Section: Discussionmentioning
confidence: 99%
“…Physiological role of CA III has turned out to be complicated, and interestingly, despite many studies the primary function of CA III is yet to be determined. To elucidate its function Kim et al, 52 created a mouse lacking a functional Car3 by gene deletion. The analysis of a knockout mouse strain (Car3 −/− ) revealed that mice lacking CA III develop normally, are fertile and have a normal life span.…”
Section: Structure and Function Of Ca IIImentioning
confidence: 99%